Implementing IBM VM Recovery Manager for IBM Power Systems - Quintero, Dino (IBM redbooks., 2019)
This IBM® Redbooks® publication describes the IBM VM Recovery Manager for Power Systems, and addresses topics to help answer customers' complex high availability (HA) and disaster recovery (DR) requirements for IBM AIX® and Linux on IBM Power Systems servers to help maximize systems' availability and resources, and provide technical documentation to transfer the how-to skills to users and support teams. The IBM VM Recovery Manager for Power Systems product is an easy to use and economical HA and DR solution. Automation software, installation services, and remote-based software support help you streamline the process of recovery, which raises availability and recovery testing, and maintains a state-of-the-art HA and DR solution. Built-in functions and IBM Support can decrease the need for expert-level skills and shorten your recovery time objective (RTO), improve your recovery point objective (RPO), optimize backups, and better manage growing data volumes. This book examines the IBM VM Recovery Manager solution, tools, documentation, and other resources that are available to help technical teams develop, implement, and support business resilience solutions in IBM VM Recovery Manager for IBM Power Systems environments. This publication targets technical professionals (consultants, technical support staff, IT Architects, and IT Specialists) who are responsible for providing HA and DR solutions and support for IBM Power Systems.